Dynamics of a cyclic task before and after a change in task constraint: horizontal bar longswing - Burton, S.; Newell, K.; Vicinanza, D.; Exell, T.; Irwin, G.; Williams, G. (ISBS Proceedings Archive (Michigan), 2020)
Returning to a consistent technique after a change in skill allows gymnasts to improve routine fluidity. This study investigates the limit cycle dynamics of the mass centre (CM) after a variation in task constraint during the horizontal bar longswing (LS). Gymnasts (n=12) from 3 different age categories completed 3 x 8 consecutive LS with LS four and five as accelerated LS. Senior gymnasts presented the most consistent limit cycle trajectory and lowest correlation dimension (CD) post- compared to pre- task constraint. Senior gymnasts displayed significantly lower CD post- constraint compared to both junior (p = .016) and development gymnasts (p< .001). The increased proficiency attributed to senior gymnasts appears to increase the stability features of the LS limit cycle of the CM angular velocity after an imposed task constraint which may indicate readiness to progress to more complex horizontal bar skills.